Gender related products: Comparing urban and rural views - Ling, Hung Kiong (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The paper explores the difference in views between urban and rural as well as male and female regarding offensive advertising. There had been lack of study on the perception of rural consumers towards advertising. The focus product category was gender related products which consists of condom, female contraceptive, female underwear, feminine hygiene product and male underwear. Investigations were made to see the level of offensiveness of the products and also their reasons of offense. A total of 300 questionnaires were distributed to respondents in urban and rural Sarawak with equal distribution between male and female in each geographical location. Results showed that rural respondents were more offended by all five gender related products and gave higher means to most of the reasons of offense compared to urban respondents. Male and female showed different views regarding the level of offensiveness of the products and the reasons that causes the offense. Condom was the most offensive product among urban and female respondents meanwhile female contraceptive offended rural and male respondents the most. Of all the reasons of offense, nudity and sexist images had been the main reason that caused offense among all the respondents in nearly all of the products. Thus, advertisers should refrain from using nudity and sexist images theme in their advertisement to increase their credibility and gain better public acceptance.